Neuromuscular mechanisms of weakness in a mouse model of chronic alcoholic myopathy. (2nd August 2022) - Moser, Samantha E.; Brown, Austin M.; Clark, Brian C.; Arnold, W. David; Baumann, Cory W.
Abstract: Background: Weakness is a common clinical symptom reported in individuals with chronic alcohol use disorder. However, it remains unclear whether low strength in these individuals is directly related to excessive ethanol intake, other deleterious factors (lifestyle, environment, genetics, etc.), or a combination of both. Therefore, we examined whether (and how) ethanol reduces the muscle's force‐producing capacity using a controlled in vivo preclinical mouse model of excessive ethanol intake. Methods: To establish whether chronic ethanol consumption causes weakness, C57BL/6 female mice consumed 20% ethanol for 40 weeks (following a 2‐week ethanol ramping period), and various measures of muscular force were quantified. Functional measures included all‐limb grip strength and in vivo contractility of the left ankle dorsiflexors and plantarflexors. Once confirmed that mice consuming ethanol were weaker than age‐matched controls, we sought to determine the potential neuromuscular mechanisms of muscle dysfunction by assessing neuromuscular excitation, muscle quantity, and muscle quality. Results: Mice consuming chronic ethanol were 13 to 16% weaker ( p ≤ 0.016) than controls (i.e., mice consuming 100% water) with the negative impact of ethanol on voluntary grip strength ( ƞ 2 = 0.603) being slightly larger than that of electrically stimulated muscle contractility ( ƞ 2 = 0.482). Relative to controls, lean mass and muscle wet masses were 9 to 16% lower in ethanol‐consuming mice ( p ≤ 0.048, ƞ 2 ≥ 0.268). No significant changes were observed between groups for indices of neuromuscular excitation at the level of the motor unit, neuromuscular junction, or plasmalemma ( p ≥ 0.259, ƞ 2 ≤ 0.097), nor was muscle quality altered after 40 weeks of 20% ethanol consumption ( p ≥ 0.695, ƞ 2 ≤ 0.012). Conclusions: Together, these findings establish that chronic ethanol consumption in mice induces a substantial weakness in vivo that we interpret to be primarily due to muscle atrophy (i.e., reduced muscle quantity) and possibly, to a lesser degree, loss of central neural drive. Abstract : Mice consuming 20% EtOH in their drinking water for 40 weeks were 13–16% weaker than control mice (no EtOH). To determine physiological mechanisms that contribute to EtOH‐induced weakness, we evaluated several markers of neuromuscular excitation, muscle quantity, and muscle quality. Our results indicate weakness after chronic EtOH consumption is primarily due to reductions in muscle quantity (i.e., atrophy) and possibly, to a lesser degree, loss of central neural drive.